Chemical Constituents from Sambucus adnata and Their Protein–Tyrosine Phosphatase 1B Inhibitory Activities - Sasaki, Tatsunori; Li, Wei; Morimura, Haruna; Li, Songpei; Li, Qin; Asada, Yoshihisa; Koike, Kazuo (Chemical & pharmaceutical bulletin, 2011)
The MeOH extract from the whole plants of Sambucus adnata has shown significant protein–tyrosine phosphatase 1B (PTP1B) inhibitory activity. Chemical study on the extract resulted in the isolation of thirteen compounds, including a novel triterpene (1). The structure of 1 was determined to be 1α,3β-dihydroxy-urs-12-en-11-one-3-yl palmitate on the basis of extensive spectroscopic analyses. Among the isolated compounds, ursolic acid, oleanolic acid and (±)-boehmenan showed the most potent PTP1B inhibitory activity in vitro with the IC50 values of 4.1, 14.4 and 43.5 μm, respectively. The kinetic analysis indicated that (±)-boehmenan inhibits PTP1B activity in a competitive manner.